Pointing Skills Training Model For Petanque Athletes - Ramdan Pelana; Yasep Setiakarnawijaya; Dwie Anggraini; Sukiri Sukiri; Intan Safitri; Rizka Antoni (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2021)
The aiming of this research and development is to produce training model of pointing skills for petanque athletes. Other than that, this research and development done for gaining in-depth information about developing and application training model of pointing skill, to knowing the effectivity, efficiency, and athlete’s interest towards the training model. The method used in this research is Research and Development (R&D) by Borg and Gall.   The instrument used in this research and development are questionnaires and Petanque pointing skills test, which were used to collect data on the results of athletes pointing. The subject in this research and development were 30 athletes of DKI Jakarta club. The results in this study is a guidebook of pointing skills for petanque athletes with a total of 30 models that have been evaluated by experts, trials and revisions, and have been tested for their effectiveness. The effectiveness test used the “t-test” technique, data taken from the pre-test and post-test result with a significance level of 0.05. Based on the result of the effectiveness test using the t-test, the difference in the results of the pointing skills between the pre test and post test obtained t0 = 14.159 bigger than tt = 0.000, so the hypothesis is rejected. In conclusion, there is a significant difference between the pre-test and post-test of the skill of pointing on petanque. The average of pre-test on pointing skills was 3.77 smaller than the post-test average of 7. This can be concluded that the pointing skills training model for petanqque athletes is effectively applied in training at the petanque sports club.